The State of Arterial Peripheral Reactivity in Patients with Autonomic Dystonia Syndrome - Villem S. Aivar, Addilyn S. Genie, Soren V. Craig (Academic Journal of Clinicians, 2023)
The most informative for the structural and functional assessment of the peripheral vascular bed are Doppler techniques (duplex scanning, Doppler ultrasound) using functional stress tests of various directions, which make it possible to study various parts of the system of regulation and activation of peripheral vascular reactions. The main advantages of these methods include their absolute non-invasiveness and safety for patients, both during single and dynamic examinations, the ability to assess blood flow parameters in real time during background observations and under the influence of specific physiological stimuli. Despite the fact that the normal physiology of peripheral vascular reactions to various stimuli (myogenic, metabolic, temperature, pain, chemical) was studied earlier, the currently existing data are mainly of an experimental nature, or are based on the results of techniques that have lost diagnostic significance (plethysmorrhaphy, capillaroscopy) and cannot be fully used in everyday clinical practice for the diagnosis of peripheral arterial disorders, primarily of neurogenic origin.The purpose of this work is a comprehensive ultrasound assessment of peripheral arterial reactivity in patients with autonomic dystonia syndrome using duplex scanning using functional myogenic load gests. metabolic. neurolo gical orientation